Governance of food security policies in India: The need for democratic governance - Ramulu, CH. Bala (2013)
The present article seeks to examine the pattern of governance designed for executing Food Security Policies in India. It deals with the need for the study on food security and the problem of food security in India and discusses the Government initiatives for ensuring food security to the people; the main provisions of the NFSB and entitlement of benefits to the people; the organisational arrangements for execution of food security policies, identify the problems that are likely to crop up in the implementation of the Bill/NFSA. An assessment of FS policies and the response on the proposed Bill/ Act; Alternative governance model for FS policies are also examined. - Reproduced.
Keywords: Food supply - India; Food supply